Primary Role of the Amygdala in Spontaneous Inflammatory Pain- Associated Activation of Pain Networks – A Chemogenetic Manganese-Enhanced MRI Approach - Arimura, Daigo; Shinohara, Kei; Takahashi, Yukari; Sugimura, Yae K.; Sugimoto, Mariko; Tsurugizawa, Tomokazu; Marumo, Keishi; Kato, Fusao (Frontiers in Neural Circuits, 2019)
Chronic pain is a major health problem, affecting 10–30% of the population in developed countries. While chronic pain is defined as “a persistent complaint of pain lasting for more than the usual period for recovery”, recently accumulated lines of evidence based on human brain imaging have revealed that chronic pain is not simply a sustained state of nociception, but rather an allostatic state established through gradually progressing plastic changes in the central nervous system. To visualize the brain activity associated with spontaneously occurring pain during the shift from acute to chronic pain under anesthetic-free conditions, we used manganese-enhanced magnetic resonance imaging (MEMRI) with a 9.4-T scanner to visualize neural activity-dependent accumulation of manganese in the brains of mice with hind paw inflammation. Time-differential analysis between 2- and 6-h after formalin injection to the left hind paw revealed a significantly increased MEMRI signal in various brain areas, including the right insular cortex, right nucleus accumbens, right globus pallidus, bilateral caudate putamen, right primary/secondary somatosensory cortex, bilateral thalamus, right amygdala, bilateral substantial nigra, and left ventral tegmental area. To analyze the role of the right amygdala in these post-formalin MEMRI signals, we repeatedly inhibited right amygdala neurons during this 2–6-h period using the “designer receptors exclusively activated by designer drugs” (DREADD) technique. Pharmacological activation of inhibitory DREADDs expressed in the right amygdala significantly attenuated MEMRI signals in the bilateral infralimbic cortex, bilateral nucleus accumbens, bilateral caudate putamen, right globus pallidus, bilateral ventral tegmental area, and bilateral substantia nigra, suggesting that the inflammatory pain-associated activation of these structures depends on the activity of the right amygdala and DREADD-expressing adjacent structures. In summary, the combined use of DREADD and MEMRI is a promising approach for revealing regions associated with spontaneous pain-associated brain activities and their causal relationships.